2020
DOI: 10.1002/uog.20406
|View full text |Cite
|
Sign up to set email alerts
|

Role of Doppler ultrasound at time of diagnosis of late‐onset fetal growth restriction in predicting adverse perinatal outcome: prospective cohort study

Abstract: KEYWORDS: adverse perinatal outcome; late fetal growth restriction; middle cerebral artery Doppler; placental cerebral ratio; umbilical artery Doppler; umbilical vein flow; uterine artery Doppler CONTRIBUTIONWhat are the novel findings of this work? In late-onset fetal growth restriction, at the time of diagnosis, only umbilical vein blood flow normalized by abdominal circumference showed moderate accuracy in predicting adverse perinatal outcome, while the diagnostic performances of both cerebroplacental ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 36 publications
(56 reference statements)
2
46
1
1
Order By: Relevance
“…Similar evidence of significant QUV reduction in FGR fetuses was shown in several previous studies on this topic [13,15,21,22]. Rigano et al [21] selected an early-FGR population with severe artery Doppler alterations.…”
Section: Discussionsupporting
confidence: 67%
“…Similar evidence of significant QUV reduction in FGR fetuses was shown in several previous studies on this topic [13,15,21,22]. Rigano et al [21] selected an early-FGR population with severe artery Doppler alterations.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, no statistically significant difference between the two groups was observed for fetal MCA S/D or PI values. This result can be interpreted as our FGR group was not exposed to the brain sparing effect or redistribution due to FGR, and it is known that late-onset FGR does not always associate with the deprived blood supply of fetal organs [17,18].…”
Section: Discussionmentioning
confidence: 72%
“…Similarly important is to avoid unnecessary interventions in false‐positive cases. In such clinical protocols, fetoplacental and uteroplacental Doppler velocimetry will have a given place 20,32 …”
Section: Discussionmentioning
confidence: 99%